An Analysis of Negative Politeness Strategy Used by Eleventh-Grade Students in English Learning at SMA Swasta Gajah Mada Medan - Jessica Talenta Panjaitan; Yessy Octavianna; Harpen Silitonga (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2025)
Communication in the school environment plays a significant role in fostering a respectful and effective learning atmosphere. However, the increasing neglect of politeness due to technological and cultural shifts has become a concern. This study aims to explore the use of negative politeness strategies by eleventh-grade students during English learning activities at SMA Swasta Gajah Mada Medan. Negative politeness, as proposed by Brown and Levinson (1987), is directed at minimizing the imposition on the listener's negative face. Using a descriptive qualitative approach, this research analyzes utterances containing negative politeness strategies from classroom interactions. The findings indicate seven types of negative politeness strategies, with